Le communalisme ou l’avenir de la Commune de 1871 - Pierre Sauvêtre; Frank Noulin; Jean-François Wagniart (Cahiers d’histoire.)
The reference to the Commune of 1871 comes back as a reference to contemporary movements, but following a usage that contrasts with those made by the left in the twentieth century. It is no longer a question of overcoming the weaknesses of the Commune, but of asking the Commune how to go beyond certain dead-ends in left-wing traditions such as left-wing republicanism, Marxism or anarchism. This is the meaning of the ongoing construction of a communalist movement, which can find in the Commune of 1871 a set of inspirations – on the substitution of a confederation of communes for the state, the self-institution of a commune which is both democratic and social, and the emancipation of women – and in the work of Murray Bookchin a theoretical contribution to define the relationship between communalism and ecology. With the worldwide development of popular assembly movements and the commons, a new communalist left is taking shape.